Vitamin D supplementation during intensive care unit stay is associated with improved outcomes in critically Ill patients with sepsis: a cohort study - Caifeng Li; Ke Zhao; Qian Ren; Lin Chen; Ying Zhang; Guolin Wang; Keliang Xie (Frontiers in Cellular and Infection Microbiology)
BackgroundPatients with vitamin D deficiency are susceptible to increased microbial infection and increased risk of mortality. However, whether vitamin D supplementation would improve their prognosis remains uncertain.MethodsWe conducted a retrospective cohort study using data from MIMIC-IV database, a publicly available database containing clinical information on patients admitted to the ICU at Beth Israel Deaconess Medical Center (BIDMC) from 2008 to 2019. Adult patients with sepsis were included in the analysis. The exposure factor was vitamin D supplementation during the ICU stay. The primary outcome was 28-day all-cause mortality. Both propensity score matching (PSM) and stepwise regression analyses were employed to adjust for potential confounders.ResultsA total of 20230 eligible patients were enrolled in the entire unmatched cohort, and 8710 patients were included in the matched cohort. In PSM analysis, the 28-day all-cause mortality rate was 14.04% (250/1780) in the vitamin D group and 22.31% (1546/6930) in the no vitamin D group. Vitamin D supplementation was associated with decreased 28-day all-cause mortality (HR, 0.56; 95% CI, 0.49-0.64; p < 0.001). Subgroup analyses showed consistent benefits regardless of the baseline vitamin D status (deficiency: HR, 0.70; 95% CI, 0.33-1.50; p = 0.36; insufficiency: HR, 0.10; 95% CI, 0.03-0.34; p < 0.001; sufficiency: HR, 0.33; 95% CI, 0.12-0.88; p = 0.03). Additionally, vitamin D supplementation was associated with decreased ICU mortality (OR, 0.37; 95% CI, 0.29-0.48; p < 0.001) and reduced in-hospital mortality (OR, 0.57; 95% CI, 0.48-0.68; p < 0.001). Sensitivity analysis using the unmatched cohort confirmed these findings (HR, 0.57; 95% CI, 0.43-0.76; p < 0.001).ConclusionsVitamin D supplementation may reduce mortality in critically ill patients with sepsis. However, further high-quality prospective studies are still needed to validate these findings.